EVALUATION OF ACADEMIC SUPERVISION AT SDN 005 TANA TIDUNG: PERSPECTIVES OF THE PRINCIPAL, TEACHERS, AND STUDENTS - Vinsensius Rixnaldi Masut; Ali Imron; Sunarni (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to evaluate the implementation of academic supervision at SDN 005 Tana Tidung from three perspectives: the principal (supervisor), the supervised teachers, and the students after the teachers received supervision. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation, while data analysis followed an interactive model consisting of data collection, data condensation, data display, and conclusion drawing/verification. The findings indicate that the supervisor carried out the evaluation of academic supervision effectively, covering aspects of effectiveness, feedback, documentation, reflection, and follow-up actions. Teachers perceived the process as beneficial for improving their teaching skills, instructional planning, professional attitudes, as well as their reflective and self-evaluative capacities. From the students’ perspective, supervision fostered a more positive learning atmosphere, enhanced motivation and satisfaction, improved learning outcomes, and contributed to a more conducive learning environment.